Optimizing intervention components for sleep promotion in children in the context of obesity prevention: the SLEEPY 2.0 study protocol - Fair, Maddy; Decker, Jessica; Fiks, Alexander G.; Mayne, Stephanie; Morales, Knashawn H.; Williamson, Ariel A.; Mitchell, Jonathan A. (Frontiers in Sleep, 2023)
Insufficient sleep duration is highly prevalent in childhood and is associated with obesity, especially among middle school children. The primary care setting has enormous potential to promote sleep, but limited time and sleep resources at in person appointments are key barriers. Digital innovations offer solutions to these barriers. Mobile health platforms can be developed to deliver behavioral sleep promotion remotely in the home setting, with tailoring to individual and contextual factors to help ensure equitable effectiveness across sociodemographic groups. This paper presents the protocol for a randomized optimization trial using the Multiphase Optimization Strategy (MOST) to develop a mobile health platform for the pediatric care setting to promote longer sleep duration for childhood obesity prevention. This is a single-site study being conducted at the Children's Hospital of Philadelphia. We will randomize 325 children, aged 8-12y, with a body mass index (BMI) between the 50th-95th percentile, and who sleep <8.5 hours per night. The Way to Health mobile platform will facilitate remote communication. A sleep tracker will estimate sleep patterns for 12-months (2-week run-in; 6-month intervention; ≈5.5-month follow-up). A randomized factorial design will assess four components: sleep goal (≥9 hours or ≥30 minutes above baseline sleep duration), digital guidance (active or active with virtual study visits), caregiver incentive (inactive or active), and performance feedback (inactive or active). Fat mass will be measured at baseline, 6-, and 12-months using dual energy X-ray absorptiometry. Total energy intake and the timing and composition of meals will be measured using 24-hour dietary recalls at baseline, 6-, and 12-months. Sociodemographic data will be measured using self-report and home addresses will be geocoded for geospatial analyses. We anticipate that this optimization trial will identify optimal component settings for sleep promotion, with clinically meaningful improvements in fat mass trajectories. Importantly, the platform will have broad impact by promoting sleep health equity across sociodemographic groups. With the optimal settings identified, we will be able to determine the effectiveness of the final intervention package under the evaluation phase of the MOST framework in a future randomized controlled trial.